Sustained release Curcumin loaded Solid Lipid Nanoparticles - Parisa Jourghanian; Solmaz Ghaffari; Mehdi Ardjmand; Setareh Haghighat; Mahdieh Mohammadnejad (Tabriz University of Medical Sciences, 2016)
Purpose: curcumin is poorly water soluble drug with low bioavailability. Use of lipid systems in lipophilic substances increases solubility and bioavailability of poorly soluble drugs. The aim of this study was to prepare curcumin loaded Solid Lipid Nanoparticles (SLNs) with high loading efficiency, small particle size and prolonged release profile with enhanced antibacterial efficacy. Methods: to synthesize stable SLNs, freeze- Drying was done using mannitol as cryoprotectant. Cholesterol was used as carrier because of good tolerability and biocompatibility. SLNs were prepared using high pressure homogenization method. Results: optimized SLNs had 112 and 163 nm particle size before and after freeze drying, respectively. The prepared SLNs had 71% loading efficiency. 90% of loaded curcumin was released after 48 hours. Morphologic study for formulation was done by taking SEM pictures of curcumin SLNs. Results show the spherical shape of curcumin SLNs. DSC studies were performed to determine prolonged release mechanism. Antimicrobial studies were done to compare the antimicrobial efficacy of curcumin SLNs with free curcumin. DSC studies showed probability of formation of hydrogen bonds between cholesterol and curcumin which resulted in prolonged release of curcumin. Lipid structure of cholesterol could cause enhanced permeability in studied bacteria to increase antibacterial characteristics of curcumin. Conclusion: the designed curcumin SLNs could be candidate for formulation of different dosage forms or cosmeceutical products.